(untitled) (Terr@ Plural, 2022)
The relationship between food and its environment has been little explored in theoretical discussions. This essay aims to search for the information that the environments insert in food, through an integrated approach, document analysis, and bibliographic research. Our experiences with food do not always bring the possibility of understanding the relationships with the environment and the dynamic processes associated with it. From the physical environment, instrumental and technological inputs, and social cultures, in mechanisms of significant complexity, food receives interference in its integrity. The abstraction of the concept as a source of hidden information on the processes is understood as something still little discussed. Aspects related to processes in soils, risks, and emerging practices were considered. It is suggested the effort to recognize the environmental, and human support, introduced in the food, to better assimilate existing relationships and sustainable behavior.